The Effectiveness of Traditional Mask Dance Rhythmic Movement Training on the Emotional Regulation Ability of Children with Mild Intellectual Disabilities - Artanty, Ary; Purwanto, Sugeng; Mulyaningsih, Farida; Kurniawan, Rubbi; Winata, Devi Catur; Ramdhana, Rickadesti; Babang, Veramyta Maria Martha (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2024)
Children with intellectual disabilities often face challenges in emotional regulation, which can adversely affect their social interactions and participation in learning activities. The traditional Tari Topeng rhythmic movement, which integrates elements of music, rhythm, and body movement, has the potential to serve as an engaging and effective intervention to support emotional development. This study aims to investigate the effectiveness of the Mask Dance (Tari Topeng), a traditional rhythmic movement form, in enhancing emotional regulation among children with mild intellectual disabilities. The research was conducted at Yayasan Putra Pancasila using a quasi-experimental method with a one-group pretest-posttest design. The participants consisted of 12 students with mild intellectual disabilities who participated in 12 Mask Dance sessions over six weeks. The research instrument utilised a validated scale for emotional regulation. A paired t-test analysis revealed a significant improvement in emotional regulation skills after the intervention (p < 0.05), particularly in adaptive regulation and a reduction of emotional lability. These findings not only suggest the effectiveness of the Mask Dance in improving emotional regulation but also highlight its cultural and aesthetic value, making it a unique and valuable therapeutic medium for strengthening socio-emotional skills in children with special needs.